2012
DOI: 10.1111/j.1939-1668.2012.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Practitioner Attitudes toward Research in Interior Design Education

Abstract: The purpose of this study was to investigate interior design practitioners' perceived attitudes toward the inclusion of research at the undergraduate and graduate levels, minimum degree requirements for practice and teaching, and the value of the graduate degree in the field of interior design. Interior design practitioners who are members of the American Society of Interior Designers (ASID) were surveyed (n = 250) using an online questionnaire based on several existing scales. The questionnaire was distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…Eighty-nine percent of respondents indicated they conducted some type of researchorientated activity. This suggests that interior design practitioners do value these activities and supports earlier studies by Birdsong & Lawlor (2001), Marsden (2012), andMartin (2004). However, some of those surveyed surmised that the majority of academic research was not useful to interior design practice.…”
Section: Perceptions Of Researchsupporting
confidence: 73%
See 2 more Smart Citations
“…Eighty-nine percent of respondents indicated they conducted some type of researchorientated activity. This suggests that interior design practitioners do value these activities and supports earlier studies by Birdsong & Lawlor (2001), Marsden (2012), andMartin (2004). However, some of those surveyed surmised that the majority of academic research was not useful to interior design practice.…”
Section: Perceptions Of Researchsupporting
confidence: 73%
“…In a quantitative study of interior designers' perceptions of professionalism, Birdsong and Lawlor (2001) found 64.9% of their sample felt research was an important component of the design profession. Dickinson, Anthony, and Marsden's (2012) survey of interior design practitioners indicated that 93% agreed that undergraduate students should know how to use research results during their design process. The same study found younger, more educated interior designers who practiced commercial design were significantly more likely to value research.…”
Section: Perceptions Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet there is also evidence that newer pedagogies may alter the degree that interior design students value design research. In a later study, the same researchers found that younger designers were more apt to appreciate design research (Dickinson, Anthony, and Marsden, 2012). So far, however, these approaches largely overlook those who may have been educated prior to the adoption of more holistic pedagogies.…”
Section: Awarenessmentioning
confidence: 96%
“…This differs from traditional academic definitions aimed at the creation of knowledge (Dickson, Anthony, & Marsden, ). A few studies relative to designers' research practices have been conducted (Dickinson, Anthony, & Marsden, ; Dickson & White, ). While these studies do provide insight into how designer practitioners approach knowledge acquisition, they are dated or focused on educational practices involving research.…”
Section: Contextmentioning
confidence: 99%